The role of boards of directors on the stability and growth of startups - Leglaiti , lakhdar; lattoui, hakim (Journal of Research in Finance and Accounting, 2026)
The purpose of this study is to provide an explicit vision for entrepreneurs, large investors, executives, academics and start-ups of the importance of forming boards to help start-ups overcome the challenges and difficulties they face, especially in the early stages before entering an accelerated growth. This study found an important role for the Board of Directors in all companies, and start-ups in particular. Through its role in the stability and growth of start-ups, helping them to overcome potential conflicts of interest within their departments and contribute to the management of potential risks.